Fate of booster biocides in aquatic ecosystem and its effects on blood cockle, Tegillarca granosa (Linnaeus, 1758) of some selected cultivation areas in Peninsular Malaysia - Mukhtar, 'Aqilah (2021)
The booster biocides are mainly used in the shipping activities, agro-industries, and domestic use. The use of booster biocides is known to cause adverse effects on marine ecosystems, including inhibiting the process of photosynthesis in marine plants, and potential to accumulate in marine organisms. In this study, booster biocides of Irgarol 1051, diuron, 3,4-dichloroaniline (3,4-DCA), and chlorothalonil were measured in blood cockle, Tegillarca granosa, and sediment from some selected cockle cultivation areas in Peninsular Malaysia. Sampling activities were conducted in Bagan Pasir in Perak, Sungai Buloh and Kampar in Selangor, and Sungai Ayam in Johor for screening the booster biocides concentrations. The liquid-liquid extraction (LLE) follow by High-Performance Liquid Chromatography (HPLC) was performed to identify the concentration of booster biocides in the collected samples. The highest Irgarol 1051 mean was found in the blood cockle with a value of 98.92 ± 13.65 μg/kg in Kapar, Selangor, while the means of diuron and its metabolites and 3,4-DCA showed the highest values of 40.31 ± 7.61 and 41.42 ± 21.58 μg/kg in Kapar, Selangor and Sungai Ayam, Johor, respectively. Sungai Ayam, Johor also exhibited the highest amount of chlorothalonil of 29.76 ± 8.80 μg/kg. The highest mean concentration of Irgarol 1051 and diuron were detected in sediment from Kapar and Sungai Buloh, Selangor, respectively that are significantly different from other locations (Tukey’s HSD, p < 0.05). Meanwhile, the highest mean concentrations of 3,4- DCA and chlorothalonil were 25.73 ± 6.40 and 23.87 ± 13.87 μg/kg, respectively which were not significantly different in locations (Tukey’s HSD, p > 0.05). Among the booster biocides detected in blood cockle and sediment, only Irgarol 1051 was significantly correlated (r=0.70, p<0.05). Referring to sediment quality guidelines, approximately 72% and more than 90% of sediment samples exceeded the environmental risk limits (ERLs) and maximum permissible concentration (MPC) for Irgarol 1051 and diuron, respectively. Thus, contaminants in marine ecosystem caused by booster biocides are highlighted as a serious problem in sediment. Increased use of biocides has the potential for bioaccumulation in food webs . Distribution and bioaccumulation of biocides were studied in selected macrobenthos from subtidal food web in the Sungai Ayam, Johor. Stable isotope carbon (δ13C) and nitrogen (δ15N) ratios were used to describe the structure of food web. Nine species of organisms including phytoplankton, zooplankton, mollusk, and crustacean were collected to represent the benthic food web in the cockle cultivation areas. Higher concentration of diuron and chlorothalonil were detected in the hermit crab, Clibanarius signatus at a concentration of 109.29 and 61.03 μg/kg wet weight, respectively, while 3,4-DCA concentration was highest in bivalve, Tegillarca granosa. The identified biomagnification factor (BMF) values indicate that biomagnification of these compounds have occurred in the studied subtidal food chain. The toxicity study of diuron in microalgae, Isochrysis galbana and blood cockle, T. granosa were conducted in short term-bioassay with the endpoints of growth performance and mortality, respectively. The 72-hours median effective concentration (EC50) and 48-hours median lethal concentration (LC50) of diuron were identified in the microalgae and blood cockle, respectively. The EC50 value for microalgae was 10.1 ppb, while LC50 for blood cockle was 1.5 ppm. The ability of the organisms to accumulate the biocides in tissues proved that I. galbana and T. granosa are potential biomonitoring organisms in marine ecosystem.